Pengaruh Metode Bermain Peran terhadap Keterampila Berbicara dalam Teks Drama pada Siswa Kelas VII SMP Negeri 20 Medan - Rodia Tammardia Siregar; Rina Devianty; Edi Saputra (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2025)
The research that has been conducted is entitled "The Effect of Role Playing Method on Speaking Skills in Drama Texts in Grade VII Students of SMP Negeri 20 Medan" which is motivated by the low learning outcomes in the Indonesian Language subject, especially in language skills. Students show a lack of self-confidence and doubt in conveying ideas or ideas that they have. The research method uses a quantitative method with a quasi-experimental approach, a non-equivalent control group design using a nonprobability sampling technique (purposive sampling) and in the form of a pre-test and post-test with a sample size of 32 students VII-1 and 32 students VII-3. Data collection techniques with observation, multiple choice tests, questionnaires, and documentation. Based on the results of the pre-test that has been carried out, it is known that the average pre-test results of the control class and the experimental class are not much different, namely the average pre-test score of the control class is 56.41 while the experimental class is 57.34. After both classes carried out the learning process with different processes, there was a significant difference in the post-test given, namely the control class obtained a score of 84.22 while the experimental class obtained a score of 89.69. Based on the dialtals, it was proven that there was an increase in learning outcomes after the learning process was carried out.